Systemic Metastase in Late Management of Group D Retinoblastoma: A Case Report - Suryawijaya, Ernes Erlyana; I Wayan Eka Sutyawan; Ni Made Ayu Surasmiati; I Made Agus Kusumadjaja (HM Publisher, 2024)
Background: Retinoblastoma (RB) is a common malignancy that affects children and is fatal if left untreated. This case report aims to raise awareness the importance of starting therapy immediately in RB patients. Case presentation: A girl aged 1 year 9 months, came with complaints that her left eye (LE) appeared white for 2 weeks. Anterior segment examination was normal. On funduscopic examination, optic nerve was difficult to evaluate, covered by a mass, multiple mass scars on the retina, a size of > 6 mm at the posterior pole, and vitreous seeding. Ultrasound examination and CT scan showed an intraocular mass with calcification. The patient was diagnosed with group D intraocular LE RB and was planned for enucleation but was postponed due to cost constraints. The patient came back after 1 year and was diagnosed with extraocular LE RB stage IVB. Conclusion: Early diagnosis without adequate therapy leads to tumor spread and reduces patient survival.